Cocriação de valor e desempenho de mercado: um estudo em lojas exclusivas do segmento de móveis planejados - Reche, Ricardo Antonio (My University, 2020)
The literature about to the co-creation of value indicates that co-created products or services have greater pricing potential and positively influence the development of new innovation strategies for products and services, due to the greater perception of value on the part of consumers, which can contribute as a link for better market performance. Through a cross-sectional survey conducted with 151 representatives of exclusive stores in the planned furniture segment and analyzed using the Structural Equation Modeling technique, the present work sought to test and empirically validate a theoretical model that related the constructs of market orientation, value co-creation, value-based pricing capabilities, product / service innovation strategies and market performance. The results showed that the market performance of the stores surveyed is explained in 39.7% by the constructs contained in the proposed model. Specifically, the study showed that four hypotheses remained confirmed: (i) the co-creation of value has a positive and significant impact on product / service innovation strategies and (ii) on pricing capacity based on value, as well as (iii) value-based pricing has a positive and significant impact on the stores' market performance, as well as (iv) innovation strategies. However, it was found that the orientation towards the market was not configured as an antecedent to the companies' co-creation processes of value and, consequently, in their market performance, rejecting two of the initial hypotheses. In addition, adopting the foundation time of shops and its profitability as moderators, the results showed that companies with a longer foundation time have greater pricing capacity based on value derived from co-creation processes, as well as younger companies had a stronger relationship transparency towards the construction of value co-creation processes. On the other hand, the moderation of profitability was not significant in terms of impact on the proposed model, that is, this boundary variable does not significantly influence the proposed relationships. As a main contribution, the research showed that the co-creation of value does not have a positive, significant and direct impact on market performance (initial hypothesis rejected), but allows a greater capacity for pricing based on value and has a positive impact on the development of strategies innovation, constructs that indirectly affect the market performance of the segment surveyed.
A literatura sobre o tema da cocriação de valor indica que produtos ou serviços cocriados apresentam maior potencial de precificação e influenciam positivamente o desenvolvimento de novas estratégias de inovação para produtos e serviços, devido à maior percepção de valor por parte dos consumidores, o que pode contribuir como elo para um melhor desempenho de mercado. Por meio de uma survey transversal realizada com 151 representantes de lojas exclusivas do segmento de móveis planejados e analisada mediante a técnica de Modelagem de Equações Estruturais, o presente trabalho buscou testar e validar empiricamente um modelo teórico que relacionasse os construtos da orientação para o mercado, cocriação de valor, capacidade de precificação baseada em valor, estratégias de inovação de produtos/serviços e desempenho de mercado. Os resultados apontaram que o desempenho de mercado das lojas pesquisadas é explicado em 39,7% pelos construtos constantes do modelo proposto. De modo específico, o estudo mostrou que quatro hipóteses restaram confirmadas: (i) a cocriação de valor impacta de forma positiva e significativa sobre as estratégias de inovação de produtos/serviços e (ii) sobre a capacidade de precificação baseada em valor, bem como (iii) a precificação baseada em valor impacta positiva e significativamente sobre o desempenho de mercado das lojas e sobre as (iv) estratégias de inovação. Porém, constatou-se que a orientação para o mercado não se configurou como um antecedente aos processos de cocriação de valor das empresas e, por conseguinte, em seu desempenho de mercado, rejeitando duas das hipóteses iniciais. Em acréscimo, adotando-se como moderadores o tempo de fundação das lojas e sua lucratividade, os resultados apontaram que empresas com maior tempo de fundação apresentam maior capacidade de precificação baseada em valor deivada dos processos de cocriação, bem como as empresas mais jovens apresentaram relação mais forte da transparência para com a construção dos processos de cocriação de valor. De outra parte, a moderação da lucratividade não se mostrou significativa em termos de impacto sobre o modelo proposto, ou seja, esta variável de contorno não influencia as relações propostas de forma importante. Como contribuição principal, a pesquisa evidenciou que a cocriação de valor não impacta de forma positiva, significativa e direta sobre o desempenho de mercado (hipótese inicial rejeitada), mas permite uma maior capacidade de precificação baseada em valor e impacta positivamente sobre o desenvolvimento de estratégias de inovação das empresas, construtos estes que incidem indiretamente sobre o desempenho de mercado do segmento pesquisado.
Keywords: Preços; Valor (Economia); Lojas de varejo; Prices; Value; Stores & shops